Developing Innovative Packaging Designs Concept for Siomay Gondrong Msmes through Kansei Engineering - Sari, Novi Purnama; Nursya'bani, Jauhariah; Sandjaja, Shafa Aisyah Pasha; Satriaji, Tegar Bayu (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2025)
Currently, Micro, Small and Medium Enterprises (MSMEs) players are competing to attract consumers to buy their products, one of which is by using attractive packaging. Siomay Gondrong is one of the MSMEs players whose packaging is not attractive, does not have a strong identity, and uses packaging that is less safe in terms of function. Based on these problems, it is necessary to develop the product packaging of Siomay Gondrong. This research aims to determine the concept and design in developing Siomay Gondrong packaging that is in accordance with consumer preferences. Kansei Engineering is used as a method to translate consumers' emotions, feelings, and desires into product design, and Principal Component Analysis (PCA) is also used as a supporting method. The total number of samples and kansei words selected as consumer references were 44 samples and 35 kansei words. After filtering with the PCA method, two packaging concept models for siomay gondrong products were identified. The two models were “Not Aesthetic - Aesthetic” and “Not Informative - Innovative”. These two concepts are retained because the values obtained in the Kaiser, Standard Deviation, and Cumulative Proportion methods are more than one (1) and have a proportion of more than 80%. Further research is needed to determine the design elements that match consumer needs using the QTT1 (quantification theory type-1) method.